(untitled) (Prosiding Keislaman dan Sains, 2025)
The digital era has changed the paradigm of education, including Islamic Religious Education (PAI). PAI learning must not only teach religious knowledge, but must also internalize character values that are relevant in the digital era. This article examines the strategy for developing PAI learning based on character education by utilizing digital technology, including the integration of technology in learning, strengthening value-based character education, and developing teacher competencies in the digital era. The results of the study show that the use of technology can increase student involvement in PAI learning, but it needs to be balanced with the development of teacher digital competencies and the formation of student characters that are resilient in facing the challenges of the digital era.